Tumour size over 3 cm predicts poor short-term outcomes after major liver resection for hilar cholangiocarcinoma. By the HC-AFC-2009 group. Issue 1 (January 2015) - Regimbeau, Jean Marc; Fuks, David; Pessaux, Patrick; Bachellier, Philippe; Chatelain, Denis; Diouf, Momar; Raventos, Artigas; Mantion, Georges; Gigot, Jean-Francois; Chiche, Laurence; Pascal, Gerard; Azoulay, Daniel; et al.
Abstract: Introduction: As mortality and morbidity after a curative resection remains high, it is essential to identify pre-operative factors associated with an early death after a major resection. Methods: Between 1998 and 2008, we selected a population of 331 patients having undergone a major hepatectomy including segment I with a lymphadenectomy and a common bile duct resection for a proven hilar cholangiocarcinoma in 21 tertiary centres. The study's objective was to identify pre-operative predictors of early death (<12 months) after a resection. Results: The study cohort consisted of 221 men and 110 women, with a median age of 61 years (range: 24–85). The post-operative mortality and morbidity rates were 8.2% and 61%, respectively. The 1-, 3- and 5-year overall survival rates were 85%, 64% and 53%, respectively. The median tumour size was 23 mm on pathology, ranging from 8 to 40. A tumour size >30 mm [odds ratio (OR) 2.471 (95% confidence interval (CI) 1.136–7.339), P = 0.001] and major post-operative complication [OR 3.369 (95% CI 1.038–10.938), P = 0.004] were independently associated with death <12 months in a multivariate analysis. Conclusion: The present analysis of a series of 331 patients with hilar cholangiocarcinoma showed that tumour size >30 mm was independently associated with death <12 months.